Diverse Synaptic Distributions of G Protein-coupled Estrogen Receptor 1 in Monkey Prefrontal Cortex with Aging and Menopause. (3rd March 2016) - Crimins, Johanna L; Wang, Athena Ching-Jung; Yuk, Frank; Puri, Rishi; Janssen, William G M; Hara, Yuko; Rapp, Peter R; Morrison, John H
Abstract: Age- and menopause-related impairment in working memory mediated by the dorsolateral prefrontal cortex (dlPFC) occurs in humans and nonhuman primates. Long-term cyclic 17β-estradiol treatment rescues cognitive deficits in aged ovariectomized rhesus monkeys while restoring highly plastic synapses. Here we tested whether distributions of G protein-coupled estrogen receptor 1 (GPER1) within monkey layer III dlPFC synapses are sensitive to age and estradiol, and coupled to cognitive function. Ovariectomized young and aged monkeys administered vehicle or estradiol were first tested on a delayed response test of working memory. Then, quantitative serial section immunoelectron microscopy was used to determine the distributions of synaptic GPER1. GPER1-containing nonperforated axospinous synapse density was reduced with age, and partially restored with estrogen treatment. The majority of synapses expressed GPER1, which was predominately localized to presynaptic cytoplasm and mitochondria. GPER1 was also abundant at plasmalemmas, and within cytoplasmic and postsynaptic density (PSD) domains of dendritic spines. GPER1 levels did not differ with age or treatment, and none of the variables examined were tightly associated with cognitive function. However, greater representation of GPER1 subjacent to the PSD accompanied higher synapse density. These data suggest that GPER1 is positioned to support diverse functions key to synaptic plasticity in monkey dlPFC.